Rationing Care through Collaboration and Shared Values - Sabin, James E. (The Hastings Center report, 2018)
Although “rationing” continues to be a dirty word for the public in health policy discourse, Nir Eyal and colleagues handle the concept exactly right in their article in this issue of the Hastings Center Report. They correctly characterize rationing as an ethical requirement, not a moral abomination. They identify the key health policy question as how rationing can best be done, not whether it should be done at all. They make a cogent defense of what they call “rationing through inconvenience” as a justifiable allocational technique. And they wisely call for research on the effectiveness and fairness of this approach and other methods of rationing. I fully agree with their approach to rationing and with their argument that the process they provocatively label “rationing through inconvenience” should not be rejected out of hand. But I believe they have underestimated two ways in which the practical impacts of rationing through inconvenience limit its potential usefulness: the asymmetry of its effect on patients and physicians and the way in which it reduces the capacity of health systems to learn from experience.